Effects of Drying Methods on the Phytochemical Contents, Antioxidant Properties, and Anti-Diabetic Activity of Nasturtium officinale R.Br. (Betong Watercress) from Southern Thailand - Praporn Kijkuokool; Irina Stepanov; Sakaewan Ounjaijean; Pimpisid Koonyosying; Kittipan Rerkasem; Hataichanok Chuljerm; Wason Parklak; Kanokwan Kulprachakarn (Life)
Nasturtium officinale R.Br. (Betong watercress) contains high levels of secondary metabolites that offer health benefits. However, fresh-cut watercress has a short shelf life. This study aimed to assess the effect of drying methods on the phytochemical contents, antioxidant activity, and anti-diabetic activity of Betong watercress. The watercress was dried using three methods: roasting (R, 50 °C, 40 min); roasting and drying (RD, 40 min roasting at 50 °C and 1 h drying at 80 °C); and blanching, roasting, and drying (BRD, 30 s blanching at 80 °C, 20 min roasting at 50 °C, and 1 h drying at 80 °C). Aqueous extracts from each drying method were analyzed for total phenolic content, total flavonoid content, total glucosinolate content, antioxidant activities (FRAP, DPPH, and ABTS assays), and α-amylase enzyme inhibition. From the results, the R method provided the highest level of total phenolic, total flavonoid, and total glucosionolate content compared to the RD and BRD methods. Similarly, antioxidant activities and α-amylase enzyme inhibition were highest in the R method, followed by the RD and BRD methods. Our results demonstrate that roasting of Betong watercress without the addition of blanching or drying effectively preserves the phytochemical contents, antioxidant activities, and anti-diabetic activity.